Time Effects on Morphology and Bonding Ability in Mercerized Natural Fibers for Composite Reinforcement - T. Williams; M. Hosur; M. Theodore; A. Netravali; V. Rangari; S. Jeelani (International Journal of Polymer Science)
Properties of cellulose-derived fibers are extremely sensitive to surface treatment. Many studies have investigated the effects of varying surface treatment parameters in natural fibers to improve fiber-matrix bonding; however, work is still needed to assist with developing better quality control methods to use these fibers in more load-bearing composites. Kenaf fibers were alkali treated, and the surface and morphology were analyzed to determine how treatment time affected the bonding sites in natural fibers. The mechanical behavior was also characterized, and tensile testing reported a 61% increase in strength and a 25% increase in modulus in fibers treated for 16 hours. The increase in tensile properties was assumed to result from increased intermolecular interaction and increased crystallinity in cellulose, which was supported by XRD. On the other hand, FTIR spectroscopy and XPS showed that the amount of hydroxyl groups needed for fiber-matrix bonding decreased at longer treatment times.